Using the Four Pillars Strategy in Playing Small Games with Varied Content and its Impact on the Aspects of Attention and Kinesthetic Intelligence for Fifth-Grade Primary School Students) - Najm, Muhammad Suhail; Mahdi, Muhammad Ghanem Ahmed (Indonesian Journal of Sport Management, 2024)
The ideal method for teaching physical education subjects is not limited to the routine method. However, some new comprehensive methods and techniques work to develop all elements of the educational institution and all aspects related to the educational process. The research aims to design a program that includes small games with various content according to the four corners strategy. Also, to reveal the effect of the educational pillars strategy in developing aspects of attention and kinesthetic intelligence among fifth-grade primary school students. For this purpose, the researchers used the experimental method to suit this research. The research population was represented by fifth-grade primary school students aged (10-12) years at Aladnaniea Primary School for Boys in Mosul in the first semester of 2022/2023. The researchers adopted the experimental and control groups' design as an experimental design with a post-test. This includes an experimental group and a control group. The research instrument consisted of tests of attention and its aspects (concentration, distribution, and shifting), and a scale of kinesthetic intelligence. The results showed that the members of the experimental group who taught according to the educational pillars strategy outperformed those of the control group, who taught according to the traditional small-game method in the tachistoscope test and the kinesthetic intelligence scale. The researchers recommended considering the gradation in the content of small games from easy to difficult and from simple to complex. Also, conducting studies similar to the current study in developing some other mental abilities.